Effect of Phosphorus Application on Fodder and Grain Yield of Oat (Avena sativa L.) in Light Soil - Yadav, J S; Singh, Jaddev; Kumar, Virendar; Yadav, H D (Annals of Arid Zone, 2016)
A field experiment was conducted during winter seasons of 1993-94 and 1994-95 at Regional Research Station, Bawal, to find out phosphorus requirement of oat for fodder as well as grain. Application of 30 kg P20S ha-1 was found optimum in respect of yield and economic returns of both forage and forage-cum-grain crop of oat. The average net return in forage-cum-grain crop was 2.75 times of forage crop (Rs. 4281 ha''). On an average, the optimum dose of phosphorus was 32.5 kg ha,l in crop grown for fodder as double-cut. But, when crop was raised for fodder-cum-grain, the optimum dose was 29.07 kg ha,1 for fodder and 32.74 kg ha-I for grain crop. The phosphorus-utilization-efficiency was appreciably higher with 30 kg P20S ha,l in comparison to 60 kg dose, but was at par with optimum dose of phosphorus.